Protocolo de uso de "Cateter venoso central" en el HNC - Bustos Fierro, Carolina; Herrera Comoglio, Raquel; Pons, Alberto; Breda, Andrea; Fernández, Guillermo; Rueda, María José; Quevedo, Débora Natalia; Pagliarone, Jonathan; Zoela, Verónica; Taborda, Bruno; Romero, Paola; Arguello, Ivana; et al. (Universidad Nacional de Córdoba. Hospital Nacional de Clínicas., 2023)
6 p. Versión 2